2019
DOI: 10.3389/fphar.2019.00588
|View full text |Cite
|
Sign up to set email alerts
|

Drugs Targeting Epigenetic Modifications and Plausible Therapeutic Strategies Against Colorectal Cancer

Abstract: Genetic variations along with epigenetic modifications of DNA are involved in colorectal cancer (CRC) development and progression. CRC is the fourth leading cause of cancer-related deaths worldwide. Initiation and progression of CRC is the cumulation of a variety of genetic and epigenetic changes in colonic epithelial cells. Colorectal carcinogenesis is associated with epigenetic aberrations including DNA methylation, histone modifications, chromatin remodeling, and non-coding RNAs. Recently, epigenetic modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 130 publications
0
73
0
1
Order By: Relevance
“…Frequently, these collaborator genes are not activated through genetic alterations, but by epigenetic mechanisms. In recent years, a number of studies suggested that drugs targeting epigenetic alterations could be applied in synergy with other anticancer therapies or, importantly, in reversing acquired therapy resistance (reviewed in [169,176,177,207,208]. However, due to the very limited tolerability of drugs targeting epigenetic mechanisms in combination with targeted therapies, most clinical trials have been disappointing so far.…”
Section: Targeting Histone Deacetylases (Hdacs)mentioning
confidence: 99%
“…Frequently, these collaborator genes are not activated through genetic alterations, but by epigenetic mechanisms. In recent years, a number of studies suggested that drugs targeting epigenetic alterations could be applied in synergy with other anticancer therapies or, importantly, in reversing acquired therapy resistance (reviewed in [169,176,177,207,208]. However, due to the very limited tolerability of drugs targeting epigenetic mechanisms in combination with targeted therapies, most clinical trials have been disappointing so far.…”
Section: Targeting Histone Deacetylases (Hdacs)mentioning
confidence: 99%
“…Despite tumour cell heterogeneity has been recognized as a bona fide engine for drug resistance [1, 3, 76], few successful approaches [17] have been proposed aimed at formulating strategies capable of quantifying the variability associated to individual cancer cell heterogeneity and minimizing its undesirable impact on clinical outcomes. Our current work accepts this challenge to provide a computational approach that allows the rational design of combinatorial therapies involving epigenetic drugs against cancer-driving chromatin modifiers [77–79].…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that P. agglomerans C1 has genes encoding enzymes (e.g., a CAT-catalase, ec 1.11.1.6) that are involved in the biosynthesis of cinnamic-related compounds from intermediates of the tryptophan pathway, and we have evidence that strain C1 produces cinnamates as well as peptides and cyclopeptides that can crosstalk with auxin ( Luziatelli et al, 2020b ). These compounds may likely play a possible regulative role in plant gene expression through epigenetic mechanisms, such as DNA methylation, histone modification (acetylation, methylation, and phosphorylation), and miRNA activation, as it already emerged in humans ( Zhu et al, 2016 ; Frolinger et al 2018 ; Arora et al, 2019 ; Carlos-Reyes et al, 2019 ; Patnaik and Anupriya, 2019 ). These mechanisms likely activate many regulatory pathways generating a response, in parallel to the pathway activated by auxin compounds, and thus establish a synergistic action.…”
Section: Discussionmentioning
confidence: 99%